2006
DOI: 10.1080/17441690500321418
|View full text |Cite
|
Sign up to set email alerts
|

Poor medicine for poor people? Assessing the impact of neoliberal reform on health care equity in a post-socialist context

Abstract: Driven in part by a resurgent interest in social inequality and health, and in part by increasing scrutiny of the social and health consequences of neoliberal economic reform, principles of health equity and social justice, the centerpieces of the Health for All strategy drafted at Alma Ata in 1978, are once again at center stage in global public health debates. Whether and how equity in access to health care can be maintained in a context of market-based health sector reform has not been systematically addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 20 publications
4
32
0
3
Order By: Relevance
“…This finding can be illustrated through the observation of repeated hospitalization events for the chronically ill and the disabled, as well as through expenditures on repeated consultations, diagnostics, laboratory testing, and the cost of pharmaceuticals (Janes et al, 2006). Similarly, (having undergone surgery) and intensive care are strongly associated with an increase in out-of-pocket payments for hospitalization.…”
Section: Results Of Model 3: Determinants Of Out-of-pocket Expenditurmentioning
confidence: 95%
“…This finding can be illustrated through the observation of repeated hospitalization events for the chronically ill and the disabled, as well as through expenditures on repeated consultations, diagnostics, laboratory testing, and the cost of pharmaceuticals (Janes et al, 2006). Similarly, (having undergone surgery) and intensive care are strongly associated with an increase in out-of-pocket payments for hospitalization.…”
Section: Results Of Model 3: Determinants Of Out-of-pocket Expenditurmentioning
confidence: 95%
“…These tendencies are also observable in posttransitional (Springer 2010) and (post)socialist contexts (Bohle and Greskovits 2007). They produce a "cacophony of socialist and neoliberal governmentality" (Bui 2015), strongly felt in the field of health (Janes et al 2006). Lincoln (2014) has shown how "healthism" and the individualization of health responsibilities played out during a 2007/2009 cholera epidemic (severe form of diarrhea) in Northern Vietnam, illustrating how "officials, media, and citizens not only identified scapegoats and proposed solutions, but also endorsed particular visions of moral conduct, social order, and public health" (Ibid.…”
Section: Individualizing Stigmatizing and Moralizing Diseasementioning
confidence: 99%
“…Agricultural sector 1 3 reform plans were not suited to the dire situation of the country at the time (Nixson et al 2000), and many were forced into a subsistence mode of production with households bearing all the risks of pastoralist production. Immediate outcomes of the privatization process combined with economic crisis were significant problems with distribution and an increase in poverty and wealth inequality (Janes and Chuluundorj 2004;Janes et al 2006;Nixson and Walters 2006;Rak and Janes 2004).…”
Section: Bayankhongor Provincementioning
confidence: 99%
“…Similarly, Janes and Chuluundorj's (2015) nationwide survey from 2001 to 2003 concluded that the difference between dzud as a climate hazard and dzud as a disaster lies in socio-economic factors and forms of governance. These authors illustrate that herders are not only managing highly variable natural environments, but also produce in fluctuating economic conditions which increase vulnerability to natural hazards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation